Koeksistensi Berbasis Moderasi Beragama: Konstruksi Keharmonisan Antar Umat Beragama di Desa Gelangkulon Ponorogo - Mahardhani, Ardhana Januar (Asketik: Jurnal Agama dan Perubahan Sosial, 2022)
The difference is the living condition in society that makes a lot of benefits, even though many frictions still result in conflict. This paper describes good practices in religious moderation that occur in Gelangkulon Village, Sampung District, Ponorogo Regency. Two different beliefs in Gelangkulon Village live side by side, and there has never been a conflict in the community. The method in this paper uses descriptive qualitative data collection in the form of observation, documentation, and in-depth interviews. The results obtained are that the excellent practice of religious moderation is essentially regulated by the government and well implemented in the Gelangkulon Village community, which can be seen from four indicators including; 1) National Moderation, 2) Tolerance, 3) Anti-Violence, and 4) Accommodative. The conclusion shows that the four indicators each show positive results in Gelangkulon Village because of the excellent synergy between the community, government, and community groups, so from this excellent synergy can see that the practice of religious moderation in Gelangkulon Village is good.